ANALISIS PEMBANGUNAN BERKELANJUTAN TERHADAP KEBIJAKAN PERUBAHAN IKLIM INDONESIA SEBAGAI UPAYA MENGAKOMODASI PARIS AGREEMENT - Halifa Haqqi, Retno Miranti, Ganjar Widhiyoga & (Transformasi, 2018)
This research explains about the Indonesian climate change policy as an effort to accommodate framework of Paris Agreement using sustainable development framework. Background of this research is the vulnerability problem cause by the climate change, such as unstable rainfall and extreme climate, which eventually will affect foods needed such as corn and rice staples. This research uses regime theory and sustainable development to explain climate change policies in Indonesia as an effort to accommodate environmental and sustainable development frameworks of Paris Agreement. The research is using qualitative method with descriptive analysis. Data source of this research is secondary data, found from books, journal and also information from electronic media. The result of this research explain that Indonesia has incorporated frameworks from Paris Agreement to its policies concerning environment and sustainable development issues.Keywords: Climate change, Paris Agreement regime, Sustainable development, Indonesian climate change policy